2021
DOI: 10.1021/acsomega.0c06316
|View full text |Cite
|
Sign up to set email alerts
|

Maltotriose–Chlorin e6 Conjugate Linked via Tetraethyleneglycol as an Advanced Photosensitizer for Photodynamic Therapy. Synthesis and Antitumor Activities against Canine and Mouse Mammary Carcinoma Cells

Abstract: Glycoconjugated chlorins represent a promising class of compounds that meet the requirements for the third-generation photosensitizer (PS) for photodynamic therapy (PDT). We have focused on the use of glucose (Glc) to improve the performance of the PS based on the Warburg effect—a phenomenon where tumors consume higher Glc levels than normal cells. However, as a matter of fact, Glc-conjugation has a poor efficacy in hydrophilic modification; thus, the resultant PS is not suitable for intravenous injection. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Gao et al reported that the Ce6-guanidine derivative associated with PDT induced apoptotic cell death in A549, the lung cancer cell line [40]. Similarly, Maltotriose-Ce6 derivatives have been shown to have both apoptotic and necrotic pathways to kill the tested breast cancer cell line (EMT6) [41]. The Bcl-2 family proteins play a crucial role in the process of cell death by apoptosis.…”
Section: Compound 17 Mediates the Pancreatic Cancer Cell Death By Int...mentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al reported that the Ce6-guanidine derivative associated with PDT induced apoptotic cell death in A549, the lung cancer cell line [40]. Similarly, Maltotriose-Ce6 derivatives have been shown to have both apoptotic and necrotic pathways to kill the tested breast cancer cell line (EMT6) [41]. The Bcl-2 family proteins play a crucial role in the process of cell death by apoptosis.…”
Section: Compound 17 Mediates the Pancreatic Cancer Cell Death By Int...mentioning
confidence: 99%
“…Pharmaceutics 2023, 15, x FOR PEER REVIEW 10 of 25apoptotic cell death in A549, the lung cancer cell line[40]. Similarly, Maltotriose-Ce6 derivatives have been shown to have both apoptotic and necrotic pathways to kill the tested breast cancer cell line (EMT6)[41].…”
mentioning
confidence: 99%
“…In this nanoparticle, HA is combined with a highly effective photosensitizer (chlorin-e6) by adipicdihydrazide (ADH) as a linker. Chlorin-e6 is a second generation photosensitizer that is able to be activated by NIR light and is used for PDT [230]. In 2014, Shi and co-workers [121] synthesized a DOX-conjugated onto poly(ethyleneimine) (PEI)-fullerene (C60-PEI-DOX) to facilitate photosynamic therapy and chemotherapy in one system as well as evaluate its synergistic effect on cancer cells.…”
Section: Application Of Polymers In Pdtmentioning
confidence: 99%
“…The cells exposed to 5 J/cm 2 of 671 nm red light suggested the antitumor activity of this photosensitizer is extremely high. Cell viability was reduced to 50% when 0.16 µM was used [165].…”
Section: In Vitro Studiesmentioning
confidence: 99%